Identifikasi Pengetahuan Teknologi Pendidikan Melalui Pelatihan ICT Berbasis Media Pembelajaran - Ahmar, Dewi Satria; Azzajjad, Muhammad Fath (Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2023)
The purpose of this ICT training is to help teachers understand and master educational technology so that they can incorporate information technology-based learning materials into the learning process. The service team found that more than 50 per cent of teachers at SD Negeri 9 Mamboro do not have sufficient technology skills to use software, applications or hardware used in learning or in technology media. This inability prevents teachers from using technology effectively in learning. Learning media-based ICT training is a favourable solution as it will help teachers acquire the necessary technological skills to overcome problems and challenges in teaching. Needs analysis, goal identification, training implementation, and evaluation are the method patterns. The training results show that SD Negeri 9 Mamboro teachers are more capable of using ICT as a learning media, with more than 50% of teachers able to use it.